Managerial economics: a mathematical approach. - Alhabeeb, M. J; Alhabeeb, M. J; Moffitt, L. J (WILEY, 2014)
Uncertainty is present in every managerial decision, and Managerial Economics: A Mathematical Approach effectively demonstrates the application of higher-level statistical tools to inform and clarify the logic of problem solving in a managerial environment. While illuminating managerial decision-making from all possible angles, this book equips readers with the tools and skills needed to recognize and address uncertainty. The book also explores individual, firm, and market-level decisions; discusses all possible risks and uncertainties encountered in the decision-making process; and prepares readers to deal with both epistemic and aleatory uncertainty in managerial decisions. Managerial Economics features: An emphasis on practical application through real-life examples and problems An accessible writing style that presents technical theories in a user-friendly way A mathematical and statistical point of view that reveals the presence of uncertainty inherent in managerial decisions Thoroughly class-tested material including problems at the end of each chapter, case study questions, review exercises, and objectives that summarize the main discussions Managerial Economics is an excellent book for upper-undergraduate and graduate-level courses in business and economics departments. The book is also an ideal reference and resource for managers, decision makers, market analysts, and researchers who require information about the theoretical and quantitative aspects of the topic.